Factors Determine Cash Waqf Participation in Kedah, Malaysia: Perception from Students in Kolej University Insaniah - Salem Al-Harethi, Abobakr Ramadhan (Universitas Islam Negeri Raden Intan Lampung, 2019)
ABSTRACT The advertisement made by the Bank Muamalat Malaysia Berhad (BMMB) was the major cause for a CashWaqf gained popularity in Malaysia partly, the first Islamic banking establishment to manage CashWaqf together with Perbadanan Wakaf Selangor (PWS). The aim of this study is to investigate the determinants of CashWaqf participation from the Malaysian perspective. This study is based on three variables used to determine factors that affect CashWaqf participation in Malaysia. The three variables that are measured in this current study are religiosity, subjective norm, and attitude.used an attitude theory as a baseline theory. The data were collected through the distribution of questionnaires to 100 participants from Students at Kolej Insaniah Universiti. Based on multiple regression analysis and other statistical techniques, the findings of the study showed a significant relationship between religiosity, subjective norm, and attitude with CashWaqf participation. Given the results from the study, it highlights some limitations and suggestions for future studies that may be conducted in this scope.Keywords: Cash Waqf, Religiosity, Subjective Norm, Attitude